Influência do lignosulfonato de sódio no processo de inibição de corrosão em meio ácido sobre aço 304l - Barbosa, João Vyctor Lima (2018)
Lignin is one of the major components of lignocellulosic biomass because of its different applicability. The present work aims at the sulfonation of the commercial Kraft lignin for the production of the sodium lignosulfonate and thus to evaluate its potential of inhibition of corrosion on the steel 304L in acid based preparation. For the sulphonation, formaldehyde and sodium sulfite were used in a reflux system to prepare a product which was characterized by infrared spectroscopy with Fourier transform, thermogravimetric analysis, differential scanning calorimetry and scanning electron miscroscopy with X-ray dispersion spectroscopy. For the study of corrosive inhibition, carboxymethylcellulose (CMC) emulsions with different concentrations of sodium lignosulfonate were prepared to be adsorbed on the steel surface by immersion. Electrochemical impedance and reverse potentiodynamic polarization tests were performed to verify the inhibition power of sodium lignosulfonate. Compounds were run in 0.1 mol L-1 HCl. It was observed that emulsions with sodium lignosulfonate and CMC are good inhibitors, but in high concentrations this result can be modified.